2021
DOI: 10.1038/s41598-021-84961-9
|View full text |Cite
|
Sign up to set email alerts
|

Increases in Great Lake winds and extreme events facilitate interbasin coupling and reduce water quality in Lake Erie

Abstract: Climate change affects physical and biogeochemical processes in lakes. We show significant increases in surface-water temperature (~ 0.5 °C decade−1; > 0.2% year−1) and wave power (> 1% year−1; the transport of energy by waves) associated with atmospheric phenomena (Atlantic Multidecadal Oscillation and Multivariate El Niño/Southern Oscillation) in the month of August between 1980 and 2018 in the Laurentian Great Lakes. A pattern in wave power, in response to extreme winds, was identified as a proxy to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 67 publications
(118 reference statements)
1
12
0
Order By: Relevance
“…The above analysis suggests the inadequacy of linear trend analysis used in previous studies (Olsen, 2019;Jabbari et al, 2021). It reinforces the complexity of wave climate in Lake Michigan.…”
Section: Wave Regime Shiftsupporting
confidence: 64%
See 2 more Smart Citations
“…The above analysis suggests the inadequacy of linear trend analysis used in previous studies (Olsen, 2019;Jabbari et al, 2021). It reinforces the complexity of wave climate in Lake Michigan.…”
Section: Wave Regime Shiftsupporting
confidence: 64%
“…Based on the data at the two offshore buoy stations, Olsen (2019) found that the measured yearly mean significant wave heights (H s > 0.25 m from May to October) from 1981 to 2017 were decreasing at the rates of 1.5 mm/yr and 3.8 mm/yr at S45002 and S45007, respectively, with 95% confidence intervals using Theil-Sen regressions. Recently, Jabbari et al (2021) investigated the trend of H s in the months of August (1980August ( -2018 at S45007 using linear regression and found an increasing trend of 2.4 mm/yr. In their data analysis, the missing wave data were filled using the empirical relation between H s and the measured wind speed (Carter, 1982).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, anthropogenic stressors are causing significant changes in the properties of lakes, such as rapid warming of surface water (O'Reilly et al, 2015), large seasonal water level fluctuations (Gronewold and Rood, 2019), increased frequency of extreme events (Saber et al, 2020), and severe water quality issues such as oxygen depletion (Rowe et al, 2019;Scavia et al, 2014) and harmful algal blooms (Brookes and Carey, 2011;Watson et al, 2016). Effort has focused on investigating the long-term responses of physical processes in lakes to climate change (O'Reilly et al, 2015;Woolway and Merchant, 2019;Jabbari et al, 2021), but improving lake monitoring and developing short-term forecast models to predict the occurrence of extreme events is also necessary (Woolway et al, 2020). The biogeochemical cycles in lakes are complex and often regulated by physical forcing; therefore, the first step to model and forecast water quality issues, such as harmful algal blooms (Paerl and Paul, 2012;O'Neil et al, 2012) and hypoxia (Rao et al, 2008(Rao et al, , 2014, is the development of accurate hydrodynamic models.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last two decades, the Great Lakes water levels have swung from record lows to extreme highs (Gronewold and Rood 2019). Higher water levels, along with more intense storms (Feng et al 2016;Jabbari et al 2021) due to the hydrologic intensification that accompanies climatic warming trends, have further exacerbated coastal flooding hazards that endanger boaters, beachgoers, and caused more severe damage to coastal infrastructure, communities and ecosystems. Recent record-breaking high lake levels in 2020 across the Great Lakes calls for the urgent need for a capable modeling framework to predict coastal flooding events and to better prepare coastal communities for emergency management and development planning.…”
Section: Introductionmentioning
confidence: 99%